Thismia gigantea, a new combination in Thismia (Thismiaceae) - Hroneš, Michal (Phytotaxa, 2014)
Thismia Griffith (1844: 221; Thismiaceae J. Agardh, 1858: 99) comprises about 55 species (e.g. Tsukaya & Okada 2012; Dančák et al. 2013; Lưu et al. 2014). The greatest species diversity is situated in southeastern Asia and in the northern parts of South America (Merckx et al. 2013). Both morphological and molecular data suggest that the genus is not monophyletic being represented by at least two evolutionary lineages, the neotropical Thismia subg. Ophiomeris (Miers) Maas & H.Maas (1986: 144) and the rest of the species in a broadly defined subg. Thismia (Merckx et al. 2006; Merckx & Smets 2014).